2016
DOI: 10.1016/j.celrep.2016.08.088
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Regulation of a Ribosome Rescue Pathway in Erythroid Cells and Platelets

Abstract: Summary Protein synthesis continues in platelets and maturing reticulocytes, although these blood cells lack nuclei and do not make new mRNA or ribosomes. Here, we analyze translation in primary human cells from both anucleate lineages by ribosome profiling and uncover dramatic accumulation of post-termination, unrecycled ribosomes in the 3´UTRs of mRNAs. We demonstrate that these ribosomes accumulate as a result of the natural loss of the ribosome recycling factor ABCE1 during terminal differentiation. Induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
136
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(154 citation statements)
references
References 65 publications
16
136
2
Order By: Relevance
“…5 Transgenic overexpression of PELO in PLPs significantly decreased the half-life of the majority of PLP mRNAs. Given that PELO expression is low in platelets, 7 these data suggest that megakaryocytes invest low levels of PELO into platelets as a mechanism for preserving mRNA levels in anucleate platelets that are incapable of transcribing new mRNA. In addition to promoting mRNA decay, the release of stalled ribosomes by PELO frees the ribosomes for additional rounds of translation.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…5 Transgenic overexpression of PELO in PLPs significantly decreased the half-life of the majority of PLP mRNAs. Given that PELO expression is low in platelets, 7 these data suggest that megakaryocytes invest low levels of PELO into platelets as a mechanism for preserving mRNA levels in anucleate platelets that are incapable of transcribing new mRNA. In addition to promoting mRNA decay, the release of stalled ribosomes by PELO frees the ribosomes for additional rounds of translation.…”
mentioning
confidence: 94%
“…In a recent report, Mills et al found that ribosomes occupy more than 6000 mRNAs in platelets. 7 In their study, they found that ribosomal footprint levels generally correlate with protein levels in platelets. 8 They also found that thrombin increases ribosomal occupancy on mRNAs, consistent with previous work demonstrating that bulk translation increases in activated platelets.…”
mentioning
confidence: 96%
See 3 more Smart Citations